HOOK RATE RAWAI DASAR LAYANGAN (RDL) STUDI PRODUKTIVITAS RAWAI DASAR YANG DIMODIFIKASI DI PERAIRAN SELAT LEMBEH BITUNG SULUT - Samuel Hamel; Karyanto Karyanto; Lusje D. Antou; Lidya Katili (JURNAL BLUEFIN FISHERIES, 2021)
The research objectives were (1) to examine the difference of productivity level of the catch (hook rate) between the flying bottom longline (RDL) and the conventional bottom longline. (2) record the type and amount of catch. The flying bottom longline (RDL) in this study is a modified construction design of bottom long line, by shortening the branch line and reducing its distance on the main line. The fishing method was changed by spreading the main line on the bottom of the sea. Thus each branch line and hooks will float to the mid surface by taking advantage of the movement of the ocean currents. The research was conducted in August-October 2020 in the waters of the Lembeh Strait, Bitung City, North Sulawesi. The research method used was 6 fishing trips trials. The results of this study indicate that the normality and homogeneity test of the hook rate data distribution is obtained 0.635 for residual value of data normality and a 0.732 of residual value of homogenity, so the data is normally distributed and homogeneous The hook rate on the flying bottom longline (RDL) operated at a depth of 10 m with fresh squid fish bait illustrates that the flying bottom longline hook rate (RDL) is higher than the conventional bottom longline (Rdk). The same thing happened at a depth of 20 m. The hook rate of the flying bottom line (RDL) was higher than that of the conventional bottom line (RDK). The effect of fresh squid bait shows a significant difference in the amount of catch between RDL and RDK. There is a significant difference between RDL and RDK when using decapterus bait. There is no significant difference between the depths of 10 meters and 20 meters on the amount of fish catch. The number of fish species caught using the flying bottom longline (RDL) is eleven species of demersal fish. Total catch using conventional bottom longlines (RDK) is eight species of demersal fish. Keywords: bait; branch line, flying bottom longline; main line, productivity